Kontribusi Petani Perempuan (Usahatani Sayuran Terhadap Pendapatan Rumahtangga Didesa Waiheru) Kecamatan Teluk Ambon Baguala - Afitu, Ketsia; Adam, Felecia P; Luhukay, Johana M (Jurnal Agrosilvopasture-Tech, 2024)
This research aims to determine the contribution of farmers to household income. The research location is Waiheru village, Teluk Ambon Baguala District. The sampling method uses a sampling technique that covers the entire population of female farmer respondents, with 30 participants. The research results show that the largest contribution from female farmers is 77%, and 100% are widows with a huge contribution to the household. In comparison, the lowest contribution percentage is 37% for household contributions. The average income provided by female farmers who focus on vegetables is around Rp. 3.287.500, while other household members have an income of Rp.5.303.988; thus, the total contribution to household income can be calculated as a percentage of 61.10%.